2015
DOI: 10.5755/j01.ct.66.1.12055
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity in Nettle (Urtica Dioica L.) and Garden Orache (Atriplex Hortensis L.) Leaves During Vegetation Period

Abstract: Straipsnyje yra analizuojamos aplinkos apsaugos politikos ištakos ir jos raida įvairiais Lietuvos istoriniais laikotarpiais. Darbe yra aptariamos Pirmosios Lietuvos Respublikos aplinkos apsaugos politikos užuomazgos, diskutuojami įvairūs požiūriai ar tai buvo politikos pradžia, ar tik klasikinė aplinkosauga. Taip pat yra vertinamas sovietinio valdymo laikotarpis, kai buvo priimtas Gamtos apsaugos įstatymas, kuris pradėjo teisiškai reglamentuoti aplinkosaugą ir nustatė pirmus svarbiausius aplinkos apsaugos vald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…The higher etanolic concentration caused higher antioxidant activities in the leaf extracts, FRAP values were the highest in April and May, then the antioxidant capacity decreased in the summer, and showed the minimum level in October. The same trend was obtained by some authors [31,32]. Table 1 summarizes the data measured for both dried leaves and roots collected at the beginning and at the end of vegetation.…”
Section: Antioxidant Capacity Of Fresh Samplessupporting
confidence: 83%
“…The higher etanolic concentration caused higher antioxidant activities in the leaf extracts, FRAP values were the highest in April and May, then the antioxidant capacity decreased in the summer, and showed the minimum level in October. The same trend was obtained by some authors [31,32]. Table 1 summarizes the data measured for both dried leaves and roots collected at the beginning and at the end of vegetation.…”
Section: Antioxidant Capacity Of Fresh Samplessupporting
confidence: 83%
“…Flavonoids, phenolic acids and other polyphenols as antioxidants can react with the free radicals of macromolecules, preventing undesirable aging processes. The high antioxidant activity of the leaves was confirmed in many of the previously described studies [ 64 , 65 ]. In addition, all the additives used can act as UV radiation absorbers, which was confirmed by UV-Vis spectroscopy analysis.…”
Section: Resultssupporting
confidence: 71%
“…On the basis of the obtained colorimetric results, it can also be observed that UV radiation caused a greater color change than the increased temperature. This is due to the presence of natural stabilizers and antioxidants in common nettle, such as carotenoids and flavonoids, that are less UV resistant [ 38 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, antiradical properties and inhibitory potential of nettle are greater than those of many synthetic antioxidants (Zeipina et al., 2015). Antioxidant activity of nettle leaves was reported to range from 17.31% to 80.77%.…”
Section: Resultsmentioning
confidence: 99%